A rubber sealing material for solid-state batteries and a method for producing the same

CN122941071APending Publication Date: 2026-10-20ZHEJIANG TRELLEBORG NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611286326.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本发明的目的是提供一种固态电池用橡胶密封材料及其制备方法,针对现有HNBR密封材料在固态电池应用中力学强度不足、压缩永久变形大、耐化学腐蚀性差以及填料吸湿导致硫化物电解质劣化的技术问题,提供一种兼具优异力学性能、低压缩永久变形、高耐腐蚀性和低吸湿性的密封材料

Benefits of technology

(1)本发明原位生成的甲基丙烯酸锌在过氧化物硫化过程中形成纳米级离子簇,构建具有动态可逆特性的离子交联网络,与过氧化物引发的共价交联网络形成双交联体系,该双交联网络结构能够在外力作用下通过离子键的可逆断裂与重组有效耗散能量,显著降低材料的压缩永久变形,赋予密封制品长期稳定的密封压力保持能力;同时,共价交联网络保障了材料在高温和化学腐蚀环境下的结构完整性,使密封材料能够在固态电池的严苛工况下维持长期可靠的密封性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of rubber sealing materials, and particularly to a rubber sealing material for solid-state batteries and its preparation method. The material comprises, by weight, 100 parts hydrogenated nitrile rubber, 20-25 parts methacrylic acid, 12-15 parts zinc oxide, 5-10 parts hydrophobically modified aramid pulp, 1-3 parts single-walled carbon nanotubes, 5-8 parts modified nano-titanium dioxide, 0.5-2 parts stearic acid, 1-3 parts antioxidant, 3-5 parts peroxide crosslinking agent, and 0.5-1.5 parts co-crosslinking agent. This invention addresses the technical problems of insufficient mechanical strength, large compression set, poor chemical corrosion resistance, and sulfide electrolyte degradation caused by filler hygroscopicity in existing rubber sealing materials used in solid-state batteries. It provides a sealing material that combines excellent mechanical properties, low compression set, high corrosion resistance, and low hygroscopicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rubber sealing materials technology, and in particular to a rubber sealing material for solid-state batteries and its preparation method. Background Technology

[0002] With the rapid development of electric vehicles and energy storage systems, solid-state batteries have attracted widespread attention due to their high energy density and high safety. Among them, sulfide all-solid-state batteries are particularly noteworthy for their high ionic conductivity (up to 10^6 Ω·cm at room temperature). -3 ~10 -2 Sulfide solid electrolytes have become a research hotspot due to their high permeability (S / cm). However, sulfide solid electrolytes are chemically extremely reactive, easily producing toxic H2S gas when exposed to water or polar solvents, and undergoing side reactions with various polar materials, leading to increased electrolyte interfacial impedance and decreased ionic conductivity. This places extremely stringent requirements on battery sealing materials: the sealing materials must not only possess excellent mechanical properties and low compression set to ensure long-term sealing reliability, but also have extremely low hygroscopicity and excellent resistance to electrolyte corrosion, while maintaining chemical compatibility with sulfide electrolytes.

[0003] Hydrogenated nitrile butadiene rubber (HNBR) is considered one of the few rubber materials chemically compatible with sulfide electrolytes due to its excellent oil resistance, heat resistance, chemical resistance, and mechanical properties. However, the mechanical and sealing properties of HNBR alone are still insufficient to meet the long-term service requirements of solid-state batteries. In existing technologies, carbon black is typically used as a reinforcing filler, but traditional carbon black-reinforced HNBR exhibits significant degradation in mechanical properties (tensile strength decreases by up to 50%) when exposed to supercritical CO2 or electrolyte corrosion, and also suffers from large compression set, making it difficult to meet the long-term sealing requirements of solid-state batteries.

[0004] Unsaturated carboxylic acid metal salts, as reactive reinforcing agents, can undergo grafting reactions with the rubber matrix during peroxide vulcanization, while simultaneously polymerizing to form nanoscale ion clusters and construct a dynamic ionic cross-linked network. This ionic cross-linked network exhibits dynamic reversibility, capable of fracturing and dissipating energy under stress, and rebonding after stress relief, endowing the material with excellent tear resistance, fatigue resistance, and low compression set. Chinese patent CN114316400A discloses a rubber-reinforced fabric membrane for hydrogen fuel cells, using HNBR and maleic anhydride-modified polybutadiene, but it mainly addresses the gas barrier requirements of hydrogen fuel cells and does not address the electrolyte corrosion resistance required for solid-state battery sealing. CN120842713A discloses a low-pressure variable electrolyte-resistant HNBR sealing material, achieving low compression set through a peroxide cross-linking system, but its reinforcing system is still mainly carbon black, resulting in limited improvement in mechanical properties and corrosion resistance. In addition, when using unsaturated carboxylic acid metal salts for reinforcement in existing technologies, pre-synthesized zinc methacrylate (ZDMA) masterbatch is often used. Its dispersion in the rubber matrix depends on the complex masterbatch preparation process, which is costly and difficult to control in terms of dispersion uniformity. Summary of the Invention

[0005] The purpose of this invention is to provide a rubber sealing material for solid-state batteries and its preparation method. Addressing the technical problems of insufficient mechanical strength, large compression set, poor chemical corrosion resistance, and sulfide electrolyte degradation caused by filler moisture absorption in existing HNBR sealing materials for solid-state battery applications, this invention provides a sealing material that combines excellent mechanical properties, low compression set, high corrosion resistance, and low moisture absorption.

[0006] To achieve the above objectives, the present invention provides a rubber sealing material for solid-state batteries, comprising, by weight, 100 parts of hydrogenated nitrile rubber, 20-25 parts of methacrylic acid, 12-15 parts of zinc oxide, 5-10 parts of hydrophobically modified aramid pulp, 1-3 parts of single-walled carbon nanotubes, 5-8 parts of modified nano-titanium dioxide, 0.5-2 parts of stearic acid, 1-3 parts of antioxidant, 3-5 parts of peroxide crosslinking agent, and 0.5-1.5 parts of co-crosslinking agent.

[0007] Preferably, the molar ratio of zinc oxide to methacrylic acid is 0.60~0.65:1. This ensures a moderate excess of zinc oxide to promote complete neutralization while avoiding excess zinc oxide remaining as an inert filler that could negatively impact performance.

[0008] In the solid-state battery rubber sealing material of this invention, zinc oxide and methacrylic acid undergo a neutralization reaction during the mixing process to generate zinc methacrylate (ZDMA) in situ. Compared with pre-synthesized ZDMA masterbatch, the in-situ generated ZDMA molecules are dispersed in the rubber matrix. During peroxide vulcanization, it grafts and copolymerizes with the hydrogenated nitrile rubber macromolecular chains and self-polymerizes to form nano-ionic clusters, constructing a uniform dynamic ionic crosslinking network.

[0009] Preferably, the antioxidant is 4,4'-bis(α,α-dimethylbenzyl)diphenylamine (antioxidant 445); the peroxide crosslinking agent is one of dicumyl peroxide (DCP) and bis-tert-butyl peroxide (BIBP); and the co-crosslinking agent is triallyl isocyanurate (TAIC).

[0010] The antioxidant is 4,4'-bis(α,α-dimethylbenzyl)diphenylamine; the peroxide crosslinking agent is one or more of dicumyl peroxide and bis-tert-butyl peroxide; and the co-crosslinking agent is triallyl isocyanurate.

[0011] Preferably, the hydrophobically modified aramid pulp is an aramid pulp that has undergone surface etching activation, nanoparticle embedding, chemical bridging and hydrophobic end-capping treatment; the modified nano titanium dioxide is nano titanium dioxide that has been surface-modified with a silane coupling agent.

[0012] More preferably, the hydrogenated nitrile rubber has a bound acrylonitrile content of 34~36wt% and a hydrogenation degree of 95% or higher.

[0013] The preparation method of the above-mentioned rubber sealing material for solid-state batteries includes the following steps: S1. The hydrogenated nitrile rubber is plasticized on a two-roll mill until it wraps around the rollers. Then zinc oxide and methacrylic acid are added in sequence and mixed. Zinc methacrylate is generated in situ to obtain a mixture. The mechanical shear and frictional heat during the mixing process promote the neutralization reaction between zinc oxide and methacrylic acid to generate zinc methacrylate in situ.

[0014] S2. Hydrophobically modified aramid pulp, single-walled carbon nanotubes, modified nano titanium dioxide, stearic acid, and antioxidant are added sequentially to the mixture of S1, and then high-shear mixing is carried out to obtain a first-stage compound. Stearic acid, as a processing aid, can improve the flowability and release properties of the compound. Antioxidant can significantly improve the heat and oxygen aging resistance of the material.

[0015] A two-stage compound is obtained by adding a peroxide crosslinking agent and a co-crosslinking agent to a first-stage compound and passing it through a thin tube multiple times. The peroxide crosslinking agent decomposes at high temperature to generate free radicals, which initiate CC covalent crosslinking between HNBR macromolecular chains, and simultaneously initiate the graft copolymerization of ZDMA with rubber chains and the polymerization of ZDMA itself. The multifunctional co-crosslinking agent TAIC can improve the crosslinking efficiency and crosslinking density.

[0016] S3. Place the two-stage compound from S2 into a flat vulcanizing machine mold for primary vulcanization, then transfer it to a forced-air drying oven for secondary vulcanization. After vulcanization, allow it to cool naturally to room temperature to obtain a rubber sealing material for solid-state batteries. Secondary vulcanization can further improve the cross-linking network, remove residual peroxide decomposition products, and enhance the material's thermal stability and compression set performance.

[0017] Preferably, in S1, the plasticizing temperature is 40~50℃, the plasticizing time is 2~5min, the mixing temperature is 60~80℃, and the mixing time is 5~8min; during the mixing process, the moisture generated by the neutralization reaction is discharged by vacuuming or by air venting through the open mill cutter, so as to avoid moisture residue affecting the vulcanization quality and the hygroscopicity of the final product.

[0018] Preferably, in S2, the high-shear mixing temperature is 60~90℃, the high-shear mixing time is 2~15min, the rotation speed is 20~60r / min, the temperature of the thin pass is 60~80℃, and the number of thin passes is 8~12.

[0019] Preferably, in step S2, the preparation of the hydrophobically modified aramid pulp includes the following steps: (1) Surface etching activation: Aramid pulp is immersed in a solution containing 5-10 wt% diammonium hydrogen phosphate, with a mass ratio of aramid pulp to solution of 0.15-0.2:1. The pulp is then heated at 40-60℃ for 30-60 min and dried to obtain activated modified aramid pulp. In this step, diammonium hydrogen phosphate chemically etches the surface of the aramid pulp under mild conditions, forming a micron-scale porous structure, increasing the specific surface area of ​​the fiber, and providing anchoring points for the subsequent embedding of nano-TiO2.

[0020] (2) Nano-TiO2 composite modification: Activated modified aramid pulp is immersed in a mixture containing 8-12 wt% ionic liquid and 1-3 wt% nano-TiO2 sol, with a mass ratio of activated modified aramid pulp to the mixture of 0.15-0.2:1. After ultrasonic treatment for 20-40 min, it is heat-treated and cured at 80-100℃ for 1-3 h, and then dried to obtain nano-TiO2 composite modified aramid pulp. The ionic liquid is 1-butyl-3-methylimidazolium chloride ([Bmim]Cl). In this step, the ionic liquid has a selective swelling effect on the amorphous region of the aramid pulp, allowing the nano-TiO2 particles to embed into the pores of the fiber surface, forming a mechanically interlocked structure. At the same time, the imidazole cations in the ionic liquid can form hydrogen bonds with the amide groups on the aramid molecular chain, further promoting the uniform loading of nano-TiO2 on the fiber surface.

[0021] (3) Chemical bridging modification: The nano-TiO2 composite modified aramid pulp was immersed in Tris buffer (pH=8.5) containing 2~5wt% silane coupling agent and 0.5~2wt% dopamine hydrochloride. The mass ratio of nano-TiO2 composite modified aramid pulp to Tris buffer was 0.15~0.2:1. Self-polymerization reaction was carried out at 25~30℃ for 10~15h, followed by drying to obtain biomimetic multi-level modified aramid pulp. The silane coupling agent was one of KH-560, KH-570 or A-151. In this step, dopamine self-polymerizes under weakly alkaline conditions to form a polydopamine (PDA) layer, which firmly adheres to the surface of aramid pulp and nano-TiO2. The alkoxy groups of the silane coupling agent undergo a condensation reaction with the hydroxyl groups on the surface of nano-TiO2, and its organic functional groups (epoxy / methacryloyloxy / vinyl) can chemically bond with the rubber matrix during the subsequent vulcanization process, thereby constructing a chemical bridging network of "polydopamine-silane coupling agent-rubber" at the fiber-rubber interface.

[0022] (4) Hydrophobic end-capping modification: The biomimetic multi-level modified aramid pulp is immersed in an anhydrous ethanol solution containing 1-3 wt% long-chain alkyl silane or fluorosilane, reacted at 40-60℃ for 4-8 h, washed and dried to obtain hydrophobic modified aramid pulp. The long-chain alkyl silane is octadecyltrimethoxysilane, and the fluorosilane is 1H,1H,2H,2H-perfluorodecyltrimethoxysilane. This step forms a dense hydrophobic barrier layer by grafting long-chain alkyl or fluorocarbon chains onto the surface of the aramid pulp, which significantly reduces the surface energy of the fiber surface, making it difficult for moisture to be adsorbed and spread on the fiber surface, thus fundamentally solving the problem of hygroscopicity of aramid pulp.

[0023] Preferably, in S2, the preparation of modified nano-titanium dioxide includes the following steps: (1) Disperse 5-10 parts by weight of nano TiO2 (particle size 10-30 nm) in 100-150 parts by weight of anhydrous ethanol and sonicate for 20-40 min to obtain nano TiO2 suspension.

[0024] (2) Under stirring, add 2-5 parts by weight of silane coupling agent to the nano-TiO2 suspension, adjust the pH to 4-5 with glacial acetic acid, and stir the reaction at 50-70℃ for 4-8 hours; the silane coupling agent is KH-560 or KH-570. Acidic conditions promote the hydrolysis of the silane coupling agent, and the generated silanol undergoes a condensation reaction with the hydroxyl groups on the surface of nano-TiO2 to form a covalently bonded organic modification layer on the surface of TiO2.

[0025] (3) After the reaction was completed, the precipitate was separated by centrifugation, washed three times with anhydrous ethanol, dried under vacuum at 80~100℃ for 6~12h, ground and sieved to obtain modified nano-titanium dioxide. The surface of the modified nano-TiO2 changed from hydrophilic to hydrophobic, and its compatibility with the hydrogenated nitrile rubber matrix was significantly improved, which can achieve uniform dispersion at the nanoscale.

[0026] Preferably, in S3, the first-stage vulcanization temperature is 165~175℃, the first-stage vulcanization time is determined according to t90 measured by the vulcanizer, the first-stage vulcanization pressure is 5~10MPa, the second-stage vulcanization temperature is 150~175℃, and the second-stage vulcanization time is 3~5h.

[0027] Therefore, the present invention, employing the aforementioned rubber sealing material for solid-state batteries and its preparation method, has the following beneficial effects: (1) The zinc methacrylate generated in situ in this invention forms nanoscale ion clusters during the peroxide sulfidation process, constructing an ion crosslinking network with dynamic reversible characteristics. It forms a double crosslinking system with the covalent crosslinking network initiated by the peroxide. This double crosslinking network structure can effectively dissipate energy through the reversible breaking and recombination of ion bonds under external force, significantly reducing the permanent compression deformation of the material and giving the sealing product a long-term stable sealing pressure retention capability. At the same time, the covalent crosslinking network ensures the structural integrity of the material under high temperature and chemical corrosion environment, enabling the sealing material to maintain long-term reliable sealing performance under the harsh working conditions of solid-state batteries.

[0028] (2) The hydrophobic modified aramid pulp of the present invention can be uniformly dispersed in the rubber matrix, significantly enhancing the bonding force of the fiber-matrix interface and giving full play to its mechanical load-bearing function as a high-performance fiber reinforcement material; at the same time, it effectively blocks the adsorption and diffusion channels of water on the fiber surface, avoiding the hydrolysis and deterioration of sulfide solid electrolyte caused by the hygroscopic absorption of hydrophilic fillers, and solving the application limitations of traditional polar reinforcement materials in sulfide systems.

[0029] (3) The rubber sealing material provided by the present invention can simultaneously meet the comprehensive requirements of solid-state batteries for sealing components in terms of mechanical strength, compression resilience, chemical resistance and environmental adaptability, and has clear industrial application value.

[0030] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0031] Figure 1 These are schematic diagrams illustrating the tensile strength of Embodiments 1-3 and Comparative Examples 1-6 of the present invention.

[0032] Figure 2 This is a schematic diagram of the elongation at break of Embodiments 1-3 and Comparative Examples 1-6 of the present invention. Detailed Implementation

[0033] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.

[0034] Example 1 The preparation method of hydrophobically modified aramid pulp includes the following steps: (1) Weigh 18g of aramid pulp, immerse it in 100g of a solution containing 7wt% diammonium hydrogen phosphate, heat it at 50℃ for 45min, and dry it to obtain activated modified aramid pulp.

[0035] (2) Weigh 18g of activated modified aramid pulp, immerse it in 100g of a mixture containing 10wt% [Bmim]Cl and 2wt% nano TiO2 sol, sonicate for 30min, heat treat at 90℃ for 2h, and dry to obtain nano TiO2 composite modified aramid pulp.

[0036] (3) Weigh 18g of nano-TiO2 composite modified aramid pulp, immerse it in 100g of Tris buffer (pH=8.5) containing 3wt% KH-570 and 1.5wt% dopamine hydrochloride, and allow it to undergo self-polymerization reaction at 27℃ for 12h, then dry it to obtain biomimetic multi-level modified aramid pulp.

[0037] (4) Weigh 18g of biomimetic multi-stage modified aramid pulp, immerse it in 100g of anhydrous ethanol solution containing 2wt% 1H,1H,2H,2H-perfluorodecyltrimethoxysilane, react at 50℃ for 6h, wash and dry to obtain hydrophobic modified aramid pulp.

[0038] The preparation method of modified nano-titanium dioxide includes the following steps: (1) Disperse 8g of nano TiO2 (particle size 20nm) in 120g of anhydrous ethanol and sonicate for 30min to obtain nano TiO2 suspension.

[0039] (2) Add 3g KH-570 to the nano TiO2 suspension under stirring, adjust the pH to 4.5 with glacial acetic acid, and stir at 60℃ for 6h. (3) After the reaction was completed, the precipitate was separated by centrifugation, washed three times with anhydrous ethanol, dried under vacuum at 90°C for 8 hours, and ground through a 200-mesh sieve to obtain modified nano titanium dioxide.

[0040] A method for preparing a rubber sealing material for solid-state batteries includes the following steps: S1. Put 100g of hydrogenated nitrile rubber on a two-roll mill and plasticize it at 45℃ for 3 minutes until it wraps around the rollers. Then add 14g of zinc oxide and 24g of methacrylic acid (molar ratio ZnO:MAA≈0.62:1) in sequence and mix at 70℃ for 6 minutes. During the mixing process, cut the air with a knife in time to generate zinc methacrylic acid in situ and obtain the mixture.

[0041] S2. Add 8g of hydrophobic modified aramid pulp, 2g of single-walled carbon nanotubes, 6g of modified nano titanium dioxide, 1g of stearic acid, and 1.5g of antioxidant 445 to the mixture of S1 in sequence, and then perform high-shear mixing at 80℃ and 40r / min for 8min to obtain a first-stage compound; add 3g of dicumyl peroxide crosslinking agent and 1g of triallyl isocyanurate co-crosslinking agent to the first-stage compound, and then pass it through a thin tube 10 times at 70℃ to obtain a second-stage compound.

[0042] S3. Place the two-stage compound of S2 into a mold of a flat vulcanizing machine and vulcanize it at 170°C for one stage. The vulcanization time is determined according to t90 measured by the vulcanizer (about 9 min). Then transfer it to a forced-air drying oven and vulcanize it at 160°C for 4 hours for the second stage. After the vulcanization is completed, let it cool naturally to room temperature to obtain the rubber sealing material for solid-state batteries.

[0043] Example 2 The preparation method of hydrophobically modified aramid pulp includes the following steps: (1) Weigh 18g of aramid pulp, immerse it in 100g of a solution containing 5wt% diammonium hydrogen phosphate, heat it at 40℃ for 30min, and dry it to obtain activated modified aramid pulp.

[0044] (2) Weigh 18g of activated modified aramid pulp, immerse it in 100g of a mixture containing 8wt% [Bmim]Cl and 1wt% nano TiO2 sol, sonicate for 30min, heat treat at 80℃ for 1h, and dry to obtain nano TiO2 composite modified aramid pulp.

[0045] (3) Weigh 18g of nano-TiO2 composite modified aramid pulp, immerse it in 100g of Tris buffer (pH=8.5) containing 2wt% KH-560 and 0.5wt% dopamine hydrochloride, and allow it to undergo a self-polymerization reaction at 25℃ for 10h. Then dry it to obtain biomimetic multi-level modified aramid pulp.

[0046] (4) Weigh 18g of biomimetic multi-stage modified aramid pulp, immerse it in 100g of anhydrous ethanol solution containing 3wt% octadecyltrimethoxysilane, react at 60℃ for 4h, wash and dry to obtain hydrophobic modified aramid pulp.

[0047] The preparation method of modified nano-titanium dioxide includes the following steps: (1) Disperse 5g of nano TiO2 (particle size 20nm) in 100g of anhydrous ethanol and sonicate for 30min to obtain nano TiO2 suspension.

[0048] (2) Add 2g KH-560 to the nano TiO2 suspension under stirring, adjust the pH to 4.0 with glacial acetic acid, and stir at 50℃ for 4h.

[0049] (3) After the reaction was completed, the precipitate was separated by centrifugation, washed three times with anhydrous ethanol, dried under vacuum at 80°C for 6 hours, and ground through a 200-mesh sieve to obtain modified nano titanium dioxide.

[0050] A method for preparing a rubber sealing material for solid-state batteries includes the following steps: S1. Put 100g of hydrogenated nitrile rubber on a two-roll mill and plasticize it at 45°C for 3 minutes until it wraps around the rollers. Then add 12g of zinc oxide and 20g of methacrylic acid (molar ratio ZnO:MAA≈0.63:1) in sequence and mix at 70°C for 6 minutes. During the mixing process, cut the air with a knife in time to generate zinc methacrylic acid in situ and obtain the mixture.

[0051] S2. Add 5g of hydrophobic modified aramid pulp, 1g of single-walled carbon nanotubes, 5g of modified nano titanium dioxide, 0.5g of stearic acid, and 1g of antioxidant 445 to the mixture of S1 in sequence. Then, perform high-shear mixing at 80℃ and 40r / min for 8min to obtain a first-stage compound. Add 3g of dicumyl peroxide crosslinking agent and 0.5g of triallyl isocyanurate co-crosslinking agent to the first-stage compound and pass it through a thin tube 10 times at 70℃ to obtain a second-stage compound.

[0052] S3 is the same as S3 in Example 1.

[0053] Example 3 The preparation method of hydrophobically modified aramid pulp includes the following steps: (1) Weigh 18g of aramid pulp, immerse it in 100g of a solution containing 10wt% diammonium hydrogen phosphate, heat it at 60℃ for 60min, and dry it to obtain activated modified aramid pulp.

[0054] (2) Weigh 18g of activated modified aramid pulp, immerse it in 100g of a mixture containing 12wt% [Bmim]Cl and 3wt% nano TiO2 sol, sonicate for 30min, heat treat at 100℃ for 3h, and dry to obtain nano TiO2 composite modified aramid pulp.

[0055] (3) Weigh 18g of nano-TiO2 composite modified aramid pulp, immerse it in 100g of Tris buffer (pH=8.5) containing 5wt% A-151 and 2wt% dopamine hydrochloride, and allow it to undergo a self-polymerization reaction at 30℃ for 15h. Then dry it to obtain biomimetic multi-level modified aramid pulp.

[0056] (4) Weigh 18g of biomimetic multi-stage modified aramid pulp, immerse it in 100g of anhydrous ethanol solution containing 1wt% 1H,1H,2H,2H-perfluorodecyltrimethoxysilane, react at 40℃ for 8h, wash and dry to obtain hydrophobic modified aramid pulp.

[0057] The preparation method of modified nano-titanium dioxide includes the following steps: (1) Disperse 10g of nano TiO2 (particle size 20nm) in 150g of anhydrous ethanol and sonicate for 30min to obtain nano TiO2 suspension.

[0058] (2) Add 5g KH-570 to the nano TiO2 suspension under stirring, adjust the pH to 5.0 with glacial acetic acid, and stir at 70℃ for 8h.

[0059] (3) After the reaction was completed, the precipitate was separated by centrifugation, washed three times with anhydrous ethanol, dried under vacuum at 100°C for 12 hours, and ground through a 200-mesh sieve to obtain modified nano titanium dioxide.

[0060] A method for preparing a rubber sealing material for solid-state batteries includes the following steps: S1. Put 100g of hydrogenated nitrile rubber on a two-roll mill and plasticize it at 45℃ for 3 minutes until it wraps around the rollers. Then add 15g of zinc oxide and 25g of methacrylic acid (molar ratio ZnO:MAA≈0.63:1) in sequence and mix at 70℃ for 6 minutes. During the mixing process, cut the air with a cutter in time to generate zinc methacrylic acid in situ, and obtain the mixture.

[0061] S2. Add 10g of hydrophobic modified aramid pulp, 3g of single-walled carbon nanotubes, 8g of modified nano titanium dioxide, 2g of stearic acid, and 3g of antioxidant 445 to the mixture of S1 in sequence. Then, perform high-shear mixing at 80℃ and 40r / min for 8min to obtain a first-stage compound. Add 4g of dicumyl peroxide crosslinking agent and 1.5g of triallyl isocyanurate co-crosslinking agent to the first-stage compound and pass it through a thin tube 10 times at 70℃ to obtain a second-stage compound.

[0062] S3. Place the two-stage compound of S2 into a flat vulcanizing machine mold and vulcanize it at 170°C for one stage. The vulcanization time is determined according to t90 measured by the vulcanizer (about 9 min). Then transfer it to a forced-air drying oven and vulcanize it at 150°C for 4 hours for the second stage. After the vulcanization is completed, let it cool naturally to room temperature to obtain the rubber sealing material for solid-state batteries.

[0063] Comparative Example 1 This comparative example is a traditional carbon black-reinforced HNBR system, without the addition of methacrylic acid, zinc oxide, hydrophobically modified aramid pulp, single-walled carbon nanotubes, and modified nano-titanium dioxide, using carbon black N220 as the reinforcing filler.

[0064] A method for preparing a hydrogenated nitrile butadiene rubber sealing material includes the following steps: S1. Put 100g of hydrogenated nitrile rubber on a two-roll mill and plasticize it at 45℃ for 3 minutes until it wraps around the rollers. Then add 50g of carbon black N220, 1g of stearic acid and 1.5g of antioxidant 445. Mix it under high shear at 80℃ and 40r / min for 8 minutes to obtain a first-stage compound.

[0065] S2. Add 3g of dicumyl peroxide crosslinking agent and 1g of triallyl isocyanurate co-crosslinking agent to the first-stage compound, and pass it through a thin stream 10 times at 70°C to obtain the second-stage compound.

[0066] S3. Place the two-stage compound of S2 into a mold of a flat vulcanizing machine and vulcanize it at 170°C for the first stage. The vulcanization time is determined according to t90 measured by the vulcanizer (about 9 min). Then transfer it to a forced-air drying oven and vulcanize it at 150°C for the second stage for 4 h. After the vulcanization is completed, let it cool naturally to room temperature to obtain hydrogenated nitrile rubber sealing material.

[0067] Comparative Example 2 This comparative example only uses the in-situ generated zinc methacrylate ion crosslinking network, without adding hydrophobically modified aramid pulp, single-walled carbon nanotubes and modified nano titanium dioxide.

[0068] A method for preparing a hydrogenated nitrile butadiene rubber sealing material includes the following steps: S1. Put 100g of hydrogenated nitrile rubber on a two-roll mill and plasticize it at 45℃ for 3 minutes until it wraps around the rollers. Then add 14g of zinc oxide and 24g of methacrylic acid (molar ratio ZnO:MAA≈0.62:1) in sequence and mix at 70℃ for 6 minutes. During the mixing process, cut the air with a knife in time to generate zinc methacrylic acid in situ and obtain the mixture.

[0069] S2. Add 1g of stearic acid and 1.5g of antioxidant 445 to the mixture of S1, and perform high-shear mixing at 80℃ and 40r / min for 8min to obtain a first-stage compound; add 3g of dicumyl peroxide crosslinking agent and 1g of triallyl isocyanurate co-crosslinking agent to the first-stage compound, and pass it through a thin tube 10 times at 70℃ to obtain a second-stage compound.

[0070] S3. Place the two-stage compound of S2 into a mold of a flat vulcanizing machine and vulcanize it at 170°C for the first stage. The vulcanization time is determined according to t90 measured by the vulcanizer (about 9 min). Then transfer it to a forced-air drying oven and vulcanize it at 150°C for the second stage for 4 h. After the vulcanization is completed, let it cool naturally to room temperature to obtain hydrogenated nitrile rubber sealing material.

[0071] Comparative Example 3 This comparative example uses an in-situ generated combination of zinc methacrylate and hydrophobically modified aramid pulp, without the addition of single-walled carbon nanotubes and modified nano-titanium dioxide. The hydrophobically modified aramid pulp is prepared using the same method as in Example 1.

[0072] A method for preparing a hydrogenated nitrile butadiene rubber sealing material includes the following steps: S1. Put 100g of hydrogenated nitrile rubber on a two-roll mill and plasticize it at 45℃ for 3 minutes until it wraps around the rollers. Then add 14g of zinc oxide and 24g of methacrylic acid (molar ratio ZnO:MAA≈0.62:1) in sequence and mix at 70℃ for 6 minutes. During the mixing process, cut the air with a knife in time to generate zinc methacrylic acid in situ and obtain the mixture.

[0073] S2. Add 8g of hydrophobic modified aramid pulp, 1g of stearic acid, and 1.5g of antioxidant 445 to the mixture of S1 in sequence, and then perform high-shear mixing at 80℃ and 40r / min for 8min to obtain a first-stage compound; add 3g of dicumyl peroxide crosslinking agent and 1g of triallyl isocyanurate co-crosslinking agent to the first-stage compound, and pass it through a thin tube 10 times at 70℃ to obtain a second-stage compound.

[0074] S3. Place the two-stage compound of S2 into a mold of a flat vulcanizing machine and vulcanize it at 170°C for the first stage. The vulcanization time is determined according to t90 measured by the vulcanizer (about 9 min). Then transfer it to a forced-air drying oven and vulcanize it at 150°C for the second stage for 4 h. After the vulcanization is completed, let it cool naturally to room temperature to obtain hydrogenated nitrile rubber sealing material.

[0075] Comparative Example 4 This comparative example uses an in-situ generated combination of zinc methacrylate, hydrophobically modified aramid pulp, and single-walled carbon nanotubes, without the addition of modified nano-titanium dioxide. The hydrophobically modified aramid pulp was prepared using the same method as in Example 1.

[0076] A method for preparing a hydrogenated nitrile butadiene rubber sealing material includes the following steps: S1. Put 100g of hydrogenated nitrile rubber on a two-roll mill and plasticize it at 45℃ for 3 minutes until it wraps around the rollers. Then add 14g of zinc oxide and 24g of methacrylic acid (molar ratio ZnO:MAA≈0.62:1) in sequence and mix at 70℃ for 6 minutes. During the mixing process, cut the air with a knife in time to generate zinc methacrylic acid in situ and obtain the mixture.

[0077] S2. Add 8g of hydrophobically modified aramid pulp, 2g of single-walled carbon nanotubes, 1g of stearic acid, and 1.5g of antioxidant 445 to the mixture of S1 in sequence, and then perform high-shear mixing at 80℃ and 40r / min for 8min to obtain a first-stage compound; add 3g of dicumyl peroxide crosslinking agent and 1g of triallyl isocyanurate co-crosslinking agent to the first-stage compound, and pass it through a thin tube 10 times at 70℃ to obtain a second-stage compound.

[0078] S3. Place the two-stage compound of S2 into a mold of a flat vulcanizing machine and vulcanize it at 170°C for the first stage. The vulcanization time is determined according to t90 measured by the vulcanizer (about 9 min). Then transfer it to a forced-air drying oven and vulcanize it at 150°C for the second stage for 4 h. After the vulcanization is completed, let it cool naturally to room temperature to obtain hydrogenated nitrile rubber sealing material.

[0079] Comparative Example 5 This comparative example uses an in-situ generated combination of zinc methacrylate, hydrophobically modified aramid pulp, single-walled carbon nanotubes, and unmodified nano-titanium dioxide. Specifically, unmodified nano-titanium dioxide replaces the modified nano-titanium dioxide in Example 1, while the remaining components and amounts are the same as in Example 1. The hydrophobically modified aramid pulp is prepared using the same method as in Example 1; the unmodified nano-titanium dioxide is virgin nano-TiO2 powder with a particle size of 20 nm, without surface modification treatment using a silane coupling agent.

[0080] A method for preparing a hydrogenated nitrile butadiene rubber sealing material includes the following steps: S1. Put 100g of hydrogenated nitrile rubber on a two-roll mill and plasticize it at 45℃ for 3 minutes until it wraps around the rollers. Then add 14g of zinc oxide and 24g of methacrylic acid (molar ratio ZnO:MAA≈0.62:1) in sequence and mix at 70℃ for 6 minutes. During the mixing process, cut the air with a knife in time to generate zinc methacrylic acid in situ and obtain the mixture.

[0081] S2. Add 8g of hydrophobically modified aramid pulp, 2g of single-walled carbon nanotubes, 6g of unmodified nano titanium dioxide, 1g of stearic acid, and 1.5g of antioxidant 445 to the mixture of S1 in sequence, and then perform high-shear mixing at 80℃ and 40r / min for 8min to obtain a first-stage compound; add 3g of dicumyl peroxide crosslinking agent and 1g of triallyl isocyanurate co-crosslinking agent to the first-stage compound, and pass it through a thin tube 10 times at 70℃ to obtain a second-stage compound.

[0082] S3. Place the two-stage compound of S2 into a mold of a flat vulcanizing machine and vulcanize it at 170°C for the first stage. The vulcanization time is determined according to t90 measured by the vulcanizer (about 9 min). Then transfer it to a forced-air drying oven and vulcanize it at 150°C for the second stage for 4 h. After the vulcanization is completed, let it cool naturally to room temperature to obtain hydrogenated nitrile rubber sealing material.

[0083] Comparative Example 6 In this comparative example, unmodified aramid pulp was used instead of the hydrophobic modified aramid pulp in Example 1, while the remaining components and amounts were the same as in Example 1. The unmodified aramid pulp was commercially available virgin aramid pulp, which had not undergone surface etching, nano-TiO2 composite, chemical bridging, or hydrophobic end-capping treatment.

[0084] A method for preparing a hydrogenated nitrile butadiene rubber sealing material includes the following steps: S1. Put 100g of hydrogenated nitrile rubber on a two-roll mill and plasticize it at 45℃ for 3 minutes until it wraps around the rollers. Then add 14g of zinc oxide and 24g of methacrylic acid (molar ratio ZnO:MAA≈0.62:1) in sequence and mix at 70℃ for 6 minutes. During the mixing process, cut the air with a knife in time to generate zinc methacrylic acid in situ and obtain the mixture.

[0085] S2. Add 8g of unmodified aramid pulp, 2g of single-walled carbon nanotubes, 6g of modified nano-titanium dioxide (prepared using the same method as in Example 1), 1g of stearic acid, and 1.5g of antioxidant 445 to the mixture in S1 in sequence. Then, perform high-shear mixing at 80°C and 40r / min for 8min to obtain a first-stage compound. Add 3g of dicumyl peroxide crosslinking agent and 1g of triallyl isocyanurate co-crosslinking agent to the first-stage compound and pass it through a thin tube 10 times at 70°C to obtain a second-stage compound.

[0086] S3. Place the two-stage compound of S2 into a mold of a flat vulcanizing machine and vulcanize it at 170°C for the first stage. The vulcanization time is determined according to t90 measured by the vulcanizer (about 9 min). Then transfer it to a forced-air drying oven and vulcanize it at 150°C for the second stage for 4 h. After the vulcanization is completed, let it cool naturally to room temperature to obtain hydrogenated nitrile rubber sealing material.

[0087] Performance testing The performance of the sealing materials prepared in Examples 1-3 and Comparative Examples 1-6 above was tested according to the following standards and methods: (1) Hardness: The Shore A hardness was determined according to GB / T531.1-2008 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber - Part 1: Shore hardness test (Shore hardness)".

[0088] (2) Tensile strength and elongation at break: According to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", type I dumbbell-shaped specimens were used, the tensile speed was 500 mm / min, and the tensile strength and elongation at break were determined at room temperature.

[0089] (3) Compression set: The compression set was determined in accordance with GB / T7759.1-2015 "Determination of compression set of vulcanized rubber or thermoplastic rubber - Part 1: Under normal and high temperature conditions", at 150℃ for 240h and 25% compression.

[0090] (4) High temperature resistance: The sample was placed in a 250℃ heat aging chamber for 2 hours, and then placed at room temperature for 24 hours. The surface was observed to see if cracks appeared.

[0091] (5) Electrolyte resistance: The material was prepared into a sealing ring (thickness 1.1 mm, outer diameter 20 mm, inner diameter 17.8 mm), compressed at 40% compression, and then immersed in dimethyl carbonate (DMC) solvent at 95°C for 9 days. After taking it out, observe whether there is any damage or breakage.

[0092] (6) Resistance to supercritical CO2 corrosion: The sample was placed in a supercritical CO2 environment of 60℃ and 7.38MPa for 144h for corrosion. The tensile strength before and after corrosion was tested and the tensile strength retention rate was calculated. At the same time, the volume change before and after corrosion was tested and the volume swelling rate was calculated.

[0093] (7) Water absorption rate: The sample was soaked in deionized water at 23℃ for 168h, and the mass change before and after soaking was tested and the water absorption rate was calculated.

[0094] The performance test results are shown in Table 1 and Figure 1-2 As shown.

[0095] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-6

[0096] From Table 1 and Figure 1-2It can be seen that the comprehensive performance of the solid-state battery rubber sealing materials prepared in Examples 1-3 is better than that of Comparative Examples 1-6. Comparative Example 1 (conventional carbon black reinforcement) has a compression set as high as 23.5%, a tensile strength retention rate of only 53.0% after SC-CO2 corrosion, a volume swelling rate as high as 28.5%, and slight cracks appear in the DMC electrolyte resistance test. This indicates that the traditional carbon black reinforcement system lacks an ion crosslinking network and a multi-level corrosion barrier, making it difficult to meet the sealing requirements of solid-state batteries. Comparative Example 2 (only in-situ ZDMA generation) has a significantly improved compression set (14.2%) compared to Comparative Example 1, but its tensile strength (26.3 MPa) and hardness (68 degrees) are lower. This indicates that the ion crosslinking network alone is insufficient to provide sufficient mechanical strength, and synergistic reinforcement with fibers and nanofillers is required. From Comparative Example 2 to Comparative Example 3 (introducing hydrophobically modified aramid pulp) and then to Comparative Example 4 (further introducing SWCNTs), the tensile strength gradually increased from 26.3 MPa to 30.5 MPa, the retention rate after SC-CO2 corrosion increased from 90.5% to 94.0%, and the volume swelling rate decreased from 12.8% to 9.8%, verifying the synergistic reinforcing effect of fiber reinforcement and SWCNT nanonetwork. Compared with Example 1, Comparative Example 5 (unmodified nano-TiO2) used unmodified nano-TiO2, and its tensile strength (29.6 MPa), retention rate after SC-CO2 corrosion (91.2%), and volume swelling rate (10.8%) were all inferior to those of Example 1. This indicates that the silane coupling agent modification of nano-TiO2 is crucial for improving its dispersibility and interfacial bonding in the HNBR matrix; the surface of unmodified TiO2 is rich in hydroxyl groups, which makes it easy to agglomerate and has weak interfacial bonding with the non-polar rubber matrix, making it difficult to fully exert the nano-dispersion reinforcement and corrosion barrier effect.

[0097] Comparative Example 6 (unmodified aramid pulp) had a water absorption rate as high as 1.25%, a retention rate of only 86.8% after SC-CO2 corrosion, and a volume swelling rate of 15.6%, which was far worse than Example 1, verifying the necessity of hydrophobic modification of aramid pulp. The polar groups such as amino and amide groups on the surface of unmodified aramid pulp not only lead to high hygroscopicity but also reduce the overall corrosion resistance of the material due to poor compatibility with the HNBR matrix and weak interfacial bonding. The water absorption rates (0.37%~0.47%) of Examples 1-3 and Comparative Examples 3-5 using hydrophobically modified aramid pulp were significantly lower than those of Comparative Examples 1-2 (0.78%~0.85%) and Comparative Example 6 (1.25%), verifying the effectiveness of the hydrophobic end-capping step in aramid pulp, which can control the overall water absorption rate of the material below 0.5 wt%.

[0098] Further, the sealing material samples of Example 1, Comparative Example 1 and Comparative Example 6 were contacted with Li6PS5Cl electrolyte powder at 60°C and 0.5MPa pressure for 48h, and the changes in the ionic conductivity of the electrolyte and the amount of H2S released were tested. The results are shown in Table 2.

[0099] Table 2. Results of sulfide electrolyte compatibility verification

[0100] As shown in Table 2, the rubber sealing material for solid-state batteries in Example 1 of this invention exhibits good chemical compatibility with the sulfide electrolyte, maintaining an ionic conductivity retention rate of 96.4%, and no H2S release was detected. In contrast, Comparative Example 1, due to the high water absorption rate of its carbon black system, and Comparative Example 6, due to the strong hydrophilicity of its unmodified aramid pulp leading to moisture release, both caused partial decomposition of the sulfide electrolyte, resulting in a significant decrease in ionic conductivity and the release of H2S gas. This further verifies the crucial role of the low hygroscopicity design of this invention in the application of sulfide solid-state batteries.

[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A rubber sealing material for solid-state batteries, characterized in that: The product comprises, by weight, 100 parts hydrogenated nitrile rubber, 20-25 parts methacrylic acid, 12-15 parts zinc oxide, 5-10 parts hydrophobically modified aramid pulp, 1-3 parts single-walled carbon nanotubes, 5-8 parts modified nano titanium dioxide, 0.5-2 parts stearic acid, 1-3 parts antioxidant, 3-5 parts peroxide crosslinking agent, and 0.5-1.5 parts co-crosslinking agent.

2. The rubber sealing material for solid-state batteries according to claim 1, characterized in that: The molar ratio of zinc oxide to methacrylic acid is 0.60~0.65:

1.

3. The rubber sealing material for solid-state batteries according to claim 1, characterized in that: The antioxidant is 4,4'-bis(α,α-dimethylbenzyl)diphenylamine; the peroxide crosslinking agent is one or more of dicumyl peroxide and bis-tert-butyl peroxide; and the co-crosslinking agent is triallyl isocyanurate.

4. The rubber sealing material for solid-state batteries according to claim 1, characterized in that: The hydrophobically modified aramid pulp is an aramid pulp that has undergone surface etching activation, nanoparticle embedding, chemical bridging, and hydrophobic end-capping treatment; the modified nano titanium dioxide is nano titanium dioxide that has been surface-modified with a silane coupling agent.

5. A method for preparing a rubber sealing material for solid-state batteries as described in any one of claims 1-4, characterized in that: Includes the following steps: S1. The hydrogenated nitrile butadiene rubber is plasticized on a two-roll mill until it wraps around the rollers, and then zinc oxide and methacrylic acid are added in sequence and mixed to generate zinc methacrylic acid in situ, thus obtaining a mixture. S2. Hydrophobically modified aramid pulp, single-walled carbon nanotubes, modified nano titanium dioxide, stearic acid, and antioxidant are added sequentially to the mixture of S1, and then high-shear mixing is carried out to obtain a first-stage compound; peroxide crosslinking agent and co-crosslinking agent are added to the first-stage compound, and after multiple thin passes, a second-stage compound is obtained. S3. Place the two-stage compound of S2 into a flat vulcanizing machine mold for first-stage vulcanization, and then transfer it to a blower drying oven for second-stage vulcanization. After vulcanization, allow it to cool naturally to room temperature to obtain a rubber sealing material for solid-state batteries.

6. The method for preparing a rubber sealing material for solid-state batteries according to claim 5, characterized in that: In S1, the plasticizing temperature is 40~50℃, the plasticizing time is 2~5min, the mixing temperature is 60~80℃, and the mixing time is 5~8min; during the mixing process, the moisture generated by the neutralization reaction is discharged by vacuuming or by venting the open mill cutter.

7. The method for preparing a rubber sealing material for solid-state batteries according to claim 5, characterized in that: In S2, the high-shear mixing temperature is 60~90℃, the high-shear mixing time is 2~15min, the rotation speed is 20~60r / min, the temperature of the thin pass is 60~80℃, and the number of thin passes is 8~12.

8. The method for preparing a rubber sealing material for solid-state batteries according to claim 5, characterized in that: In S2, the preparation of hydrophobically modified aramid pulp includes the following steps: (1) Immerse aramid pulp in a solution containing 5-10 wt% diammonium hydrogen phosphate, with a mass ratio of aramid pulp to solution of 0.15-0.2:1, heat at 40-60℃ for 30-60 min, and dry to obtain activated modified aramid pulp; (2) The activated modified aramid pulp was immersed in a mixture containing 8-12 wt% ionic liquid and 1-3 wt% nano TiO2 sol, with the mass ratio of activated modified aramid pulp to the mixture being 0.15-0.2:

1. The pulp was ultrasonically treated for 20-40 min, heat-treated and cured at 80-100℃ for 1-3 h, and then dried to obtain nano TiO2 composite modified aramid pulp. The ionic liquid was 1-butyl-3-methylimidazolium chloride. (3) The nano-TiO2 composite modified aramid pulp is immersed in a Tris buffer containing 2-5 wt% silane coupling agent and 0.5-2 wt% dopamine hydrochloride. The mass ratio of nano-TiO2 composite modified aramid pulp to Tris buffer is 0.15-0.2:

1. The self-polymerization reaction is carried out at 25-30℃ for 10-15 h. After drying, biomimetic multi-level modified aramid pulp is obtained. The silane coupling agent is one of KH-560, KH-570 or A-151. (4) Immerse the biomimetic multi-level modified aramid pulp in an anhydrous ethanol solution containing 1-3 wt% long-chain alkyl silane or fluorosilane, react at 40-60℃ for 4-8 h, wash and dry to obtain hydrophobic modified aramid pulp; the long-chain alkyl silane is octadecyltrimethoxysilane, and the fluorosilane is 1H,1H,2H,2H-perfluorodecyltrimethoxysilane.

9. The method for preparing a rubber sealing material for solid-state batteries according to claim 5, characterized in that: In S2, the preparation of modified nano-titanium dioxide includes the following steps: (1) Disperse 5-10 parts by weight of nano TiO2 in 100-150 parts by weight of anhydrous ethanol and sonicate for 20-40 min to obtain nano TiO2 suspension; (2) Add 2-5 parts by weight of silane coupling agent to the nano TiO2 suspension under stirring, adjust the pH to 4-5 with glacial acetic acid, and stir the reaction at 50-70℃ for 4-8h; the silane coupling agent is KH-560 or KH-570. (3) After the reaction is completed, the precipitate is separated by centrifugation, washed with anhydrous ethanol, dried under vacuum at 80~100℃ for 6~12h, ground and sieved to obtain modified nano titanium dioxide.

10. The method for preparing a rubber sealing material for solid-state batteries according to claim 5, characterized in that: In S3, the first-stage vulcanization temperature is 165~175℃, the first-stage vulcanization time is determined according to t90 measured by the vulcanizer, the first-stage vulcanization pressure is 5~10MPa, the second-stage vulcanization temperature is 150~175℃, and the second-stage vulcanization time is 3~5h.

Citation Information

Patent Citations

  • Rubber cloth diaphragm for hydrogen fuel cell and preparation method of rubber cloth diaphragm

    CN114316400A

  • Low-voltage-change electrolyte-resistant HNBR sealing material and preparation method thereof

    CN120842713A